HETEROGENEIDAD EN LA RECUPERACIÓN ECOLÓGICA DE BOSQUES SECUNDARIOS POST-GANADERÍA EN IQUITOS, AMAZONÍA PERUANA - VIZCARRA BENTOS, Tony (2025)
The degradation of Amazonian landscapes due to extensive cattle ranching is a widely recognized problem, but restoration actions are still insufficient, partly due to the limited understanding of the processes that drive the recovery of their ecological integrity. This study evaluated the natural recovery of post-grazing secondary forests in an area near Iquitos (Peruvian Amazon), analyzing ecological integrity through species composition and diversity, recruitment, and basal area, in relation to land use intensity and the structure of the surrounding landscape. Ecological indicators of all trees and palms with a diameter at breast height (DBH) ≥ 3 cm were recorded in ten 500 m² plots with ages between 17 and 38 years of secondary succession. The results revealed low values of species richness (17-28 species) and basal area (0.56-1.47 m²). The analysis of these indicators showed heterogeneity in natural regeneration, identifying two groups of plots with significantly different floristic and structural characteristics. These findings confirm the negative impact of extensive cattle ranching on secondary succession and demonstrate that natural recovery in these forests is not uniform but is strongly conditioned by the intensity of land use and landscape configuration, particularly proximity to and percentage cover of primary forest. This information is fundamental for the design of effective restoration strategies in the context of the Amazonian landscape.